Penanaman Nilai Kepahlawanan dalam Pembelajaran IPS di SMP N 2 Medan - Aulina Rahmi Lubis; Azizah Nurul Iman; Indri Cornelia Sitanggang; Syahrul Nizar Saragih (BEST Journal (Biology Education, Sains and Technology), 2022)
Junior secondary education has an important role in efforts to improve the quality of human resources both in the intellectual, emotional, social, and spiritual fields. Good learning planning in Social Sciences (IPS) subjects at SMP Negeri 2 Medan about the cultivation of heroic values is important for teachers to realize. Specifically, this paper aims to describe how teachers instill heroic values in social studies learning, especially in the preparation of social studies learning implementation plans (RPP) for the cultivation of junior high school heroic values and there are also several examples of social studies learning models in junior high schools that can be applied by educators in immersing heroic values. The focus of this article is a conceptual study of the value of heroism in social studies learning in junior high schools.